FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU PASIEN TB MDR DALAM PENCEGAHAN PENULARAN TB MDR DI WILAYAH KERJA PUSKESMAS KOTA SEMARANG - Asnia Uliya Devi; Kusyogo Cahyo; Zahroh Shaluhiyah (Jurnal Kesehatan Masyarakat (Undip), 2019)
Every year, the population of Semarang City increases. This causes population density so that the disease is very easy to breed, especially TB disease. Treatment of incomplete TB causes resistance to antituberculosis drugs. This is what makes the emergence of MDR TB disease. The way to transmit MDR TB disease causes the behavior of MDR TB patients to greatly influence the transmission of MDR TB disease. This study aims to analyze the factors related to the behavior of MDR TB patients in the prevention of transmission of MDR TB in the Semarang City Health Center Working Area. The method used is quantitative with cross sectional approach. The population in this study were MDR TB patients in 2017 until May 2018 in the Semarang City Health Center Working Area. This study uses univariate and bivariate analysis using the Chi-Square test. The results showed that there was a relationship between knowledge about MDR TB (p = 0.020), respondents' attitudes toward prevention of transmission of MDR TB (p = 0.004), accessibility of information on MDR TB (p = 0.001), and family support (p = 0.019) with behavior MDR TB patients in the prevention of transmission of MDR TB. It is necessary to improve prevention of transmission of MDR TB and compliance with medication so that people around MDR TB patients will not be easily infected and patients can recover from MDR TB.